Estimation of Attraction of External Sources of Financing in Economy of Ukraine - Inna Berzhanir; Anatolii Berzhanir; Liubov Shachkovska; Bondaruk Ihor; Osadchuk Nataliia (Communications of International Proceedings, 2021)
External sources of financing allow domestic economic entities to form sufficient amounts of financial capital to ensure the possibility of expanding their activities, the prospects of entering international markets. The most attractive form of investment in Ukraine is foreign direct investment, but given the negative trends of recent years, it is advisable to improve the country's investment attractiveness through direct state participation in ensuring the protection and security of investors, forming an effective investment strategy, harmonizing domestic legislation with EU standards, which in turn will increase FDI inflows. The main problems of low levels of foreign investment in Ukraine are the small amount of capital expenditures of domestic budgets compared to developed countries, differences in the timing of investment projects and budget planning, limited impact of public investment on economic growth, corruption in investment projects etc. Directions for improving Ukraine's investment attractiveness for foreign investors may be: reducing pressure on investors and the lack of diversified sources of investment; attracting investments in industries that are particularly in need of investment; encouraging business entities to long-term investments, as well as to reinvest, stability of investment legislation and providing warranties to investors.
Keywords: Capital Investments; Foreign Direct Investment; State Budget.